Prepričanja in implementacija na dokazih podprte prakse med visokošolsko izobraženimi diplomiranimi medicinskimi sestrami in zdravstveniki v Sloveniji (1. del) - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2022)
Introduction: Planning the strategy of evidence-based care implementation in Slovenian nursing calls for an assessment of knowledge, beliefs, and various aspects of evidence-based care implementation among nursing care providers. The assessment should be reliable, valid and representative in order to be used for the planning of national strategies in this field. The aim of the article is to present the psychometric analysis results of the internationally-renowned instrument used.Methods: A total of 1,014 nurses with a higher education degree from all three levels of health care participated in the research. Two established scales were used in the research: Evidence-Based Practice Beliefs Scale and Evidence-Based Practice Implementation Scale. A psychometric analysis of the data was conducted using reliable, valid tests.Results: The mean value for evidence-based practice beliefs was 3.47 (s = 0.54). Reliability of the scale was 0.909, the variance was explained in 63.71% with three factors (beliefs in knowledge; beliefs in usefulness; difficulty of implementation and time efficiency). The mean value for implementation was 2.23 (s = 0.89). Reliability of the scale was 0.969, the variance was explained in 68.52% with two factors (application of knowledge; application of implementation steps).Discussion and conclusion: The tested instruments have proven to be reliable and valid.Research results clearly demonstrate insufficient knowledge for the development of evidence-based practice and knowledge that is required for daily development activities implemented by nurses with a higher education degree. Steps should be taken to improve the situation in higher education institutions, healthcare institutions, and at the level of national nursing associations.
Keywords: change; clinical expertise; improvements; izboljšave; klinična ekspertiza; knowledge; nursing; pacienti; patients; raziskave; research; spremembe; zdravstvena nega; znanje